Guidelines for the management of extravasation - Kim, Jung Tae; Park, Jeong Yun; Lee, Hyun Jung; Cheon, Young Ju (Journal of educational evaluation for health professions, 2020)
The purpose of these practice guidelines is to offer and share strategies for preventing extravasation and measures for handling drugs known to cause tissue necrosis, which may occur even with the most skilled experts at intravenous (IV) injection. Herein, general knowledge about extravasation is first described, including its definition, incidence, risk factors, diagnosis, differential diagnosis, and extravasation injuries. Management of extravasation includes nursing intervention and thermal application. At the first sign of extravasation, nursing intervention with following steps is recommended: stop administration of IV fluids immediately, disconnect the IV tube from the cannula, aspirate any remaining drug from the cannula, administer drug-specific antidote, and notify the physician. Local thermal treatments are used to decrease the site reaction and absorption of the infiltrate. Local cooling (ice packs) aids in vasoconstriction, theoretically limiting the drug dispersion. Although clear benefit has not been demonstrated with thermal applications, it remains a standard supportive care. The recommended application schedule for both warm and cold applications is 15 to 20 minutes, every 4 hours, for 24 to 48 hours. For prevention of extravasation, health professionals should be familiar with the extravasation management standard guidelines. They should regularly check the extravasation kit, assess patients’ sensory changes, tingling or burning, and always pay attention to patients’ words. The medical team’s continuous education on extravasation is essential. With the practical use of these guidelines, it is expected to reduce the occurrence rate of extravasation and contribute to patient care improvement.